DFT Study of Proton Transfer in Methyl Urocanate and Butyl Urocanate. Issue 1 (25th August 2015) - Yana, Janchai; Chirachanchai, Suwabun; Jarumaneeroj, Chatchai; Lee, Vannajan Sanghiran; Kodchakorn, Kanchanok; Tashiro, Kohji; Nimmanpipug, Piyarat; Chirachanchai, Sawabu; Hoven, Voravee; Sojamsang, Warayuth
Summary Development of proton conductivity is necessary to improve polymer electrolyte efficiency of proton exchange membrane fuel cell (PEMFC) which is alternative environmentally friendly resource. Modification of polymer electrolyte has been employed using water free polymer instead of hydrated polymer membrane to disregard water loss problem at high temperature. Heterocycles such as imidazole and benzimidazole derivatives was considered for anhydrous membrane modification to encourage proton transfer in polymer electrolyte membrane. Alkyl urocanate was interested as a vehicle for proton transfer between side chains of polymer membrane. In this work, investigation of blending of butyl urocanate in polymer membrane to assist the proton transfer ability was carried out. Energy barrier of proton movement between alkyl urocanate was calculated. The preferred orientation of bimolecular alkyl urocanaetes was initiated by crystallographic data. The energies of various proton position in between neighbouring molecules were calculated to determine the barrier of proton transfer. The density function theory (DFT) with generalized gradient approximation (GGA) and BLYP function was used for calculation. The energy barrier of butyl urocanate was found lower than methyl urocanate corresponding to the previous experimental proton conductivity data.